2006
DOI: 10.1002/pmic.200402086
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteome approach to characterize the high‐pressure stress response of Lactobacillus sanfranciscensis DSM 20451T

Abstract: High hydrostatic pressure (HHP) exerts diverse effects on microorganisms, leading to stress response and cell death. While inactivation of microorganisms by lethal HHP is well investigated in the context of food preservation and the hygienic safety of minimal food processes, sublethal HHP stress response and its effect on adaptation and cross-protection is less understood. In this study, the HHP stress response of Lactobacillus sanfranciscensis was characterized and compared with cold, heat, salt, acid and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 43 publications
1
38
0
2
Order By: Relevance
“…T led to overexpression of proteins which had sequence homologies with heat shock proteins encoded by dnaK and groEL and with clp-encoded proteases (42). The results of the present study show that the overexpression of the molecular chaperones and proteases responds to diamide stress in a similar way in L. sanfranciscensis DSM 20451…”
Section: High-pressure Treatment Of L Sanfranciscensis Dsm 20451supporting
confidence: 53%
“…T led to overexpression of proteins which had sequence homologies with heat shock proteins encoded by dnaK and groEL and with clp-encoded proteases (42). The results of the present study show that the overexpression of the molecular chaperones and proteases responds to diamide stress in a similar way in L. sanfranciscensis DSM 20451…”
Section: High-pressure Treatment Of L Sanfranciscensis Dsm 20451supporting
confidence: 53%
“…The system consists of DnaK, its cochaperone (DnaJ), and a nucleotide exchange factor (GrpE) (286). Expression analyses conducted at the transcript and/or protein level revealed that production of DnaK is induced in different LAB under diverse stress conditions (287)(288)(289)(290). A deletion in dnaK resulted in a thermosensitive phenotype for Lc.…”
Section: Treating Damaged Macromoleculesmentioning
confidence: 99%
“…GroES is the most abundant protein in B. subtilis, with some 500,000 molecules per cell after 30 min of exposure to heat stress (295). The production of the highly conserved GroEL and GroES proteins is activated under various stress conditions in LAB (287)(288)(289)(290)296).…”
Section: Treating Damaged Macromoleculesmentioning
confidence: 99%
“…This analysis could be also performed to compare the effects that new technologies produce on bacteria comparing with the normal stress conditions. In fact, the HHP stress response of L. sanfranciscensis was compared with cold, heat, salt, acid and starvation stresses responses [18].…”
Section: Methodological Approaches To Study the Effects Of Stress On Labmentioning
confidence: 99%
“…Several proteins are induced after high pressure treatment and some of these have also been involved in the response to other various stresses [8]. The responses to HHP stress have been studied in particular on L. sakei and L. sanfranciscensis [73,18]. These Authors suggested the presence of de novo protein synthesis as a consequence of HHP stress [73].…”
Section: Osmotic Stress Responsementioning
confidence: 99%